The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1164/ajrccm.165.7.2103049
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory Asynchrony in Proportional Assist Ventilation

Abstract: One of the proposed advantages of proportional assist ventilation (PAV) has been the automatic synchrony between the end of the patient's inspiratory effort and the ventilator cycle (i.e., expiratory synchrony). However, recent clinical studies have shown a prolonged ventilator inspiratory time or even a "runaway" phenomenon with the normal use of PAV. We hypothesize that control-system delay may account for this, because in reality there is always some degree of delays between control-system's input and outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
0
12
0
5
Order By: Relevance
“…During PAV, the ventilator assistance is delivered in proportion to the patient's instantaneous flow and volume, by compensating patient resistive and elastic loads, thus amplifying the patient's own effort breath by breath [10]. Several studies showed that PAV improves patient-ventilator synchrony at the start of inspiration [11][12][13] but not necessarily at the end of inspiration [13][14][15]. Moreover, its widespread clinical use was limited by the necessity of regular measurements of respiratory mechanics (elastance and resistance).…”
Section: Introductionmentioning
confidence: 99%
“…During PAV, the ventilator assistance is delivered in proportion to the patient's instantaneous flow and volume, by compensating patient resistive and elastic loads, thus amplifying the patient's own effort breath by breath [10]. Several studies showed that PAV improves patient-ventilator synchrony at the start of inspiration [11][12][13] but not necessarily at the end of inspiration [13][14][15]. Moreover, its widespread clinical use was limited by the necessity of regular measurements of respiratory mechanics (elastance and resistance).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] The reason for multiple studies of flow cycling is attributed to the universal adoption of spontaneous breathing modes such as pressure-support ventilation (PSV). 17 During PSV the patient both triggers and cycles the breath (Fig.…”
Section: Flow Cyclingmentioning
confidence: 99%
“…7,10 Failure to take this into account during FAV may lead to under-assistance as well as over-assistance, resulting in patient-ventilator asynchrony, frequent alarms, and increased caregiver intervention. 1,2,5,11,12 Clinical acceptance of PAV has been disappointing as a result of such considerations. 13,14 Automatic tube compensation (ATC) is a ventilatory modality designed to overcome the added flow resistance of an artificial airway by applying positive pressure in relationship to flow based on in vitro determination of tube resistance and continuous measurement of inspiratory flow and airway opening pressure (Pao) during pressure preset modes of ventilation.…”
Section: P Roportional Assist Ventilation (Pav) Is a Novel Mode Of Pamentioning
confidence: 99%